Paroxysmal Tonic Upgaze: Age of Onset and Prognosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Six children who developed paroxysmal tonic upgaze (PTU) at 2.6 to 7.4 years of age were examined at least once per year for a 10 year period of follow-up at the Departments of Paediatrics and Ophthalmology, University of Chieti, Italy.